Multipositional and transnational members of the Hungarian economic elite at the end of the 1990s: Their social characteristics and income chances - György Lengyel (Journal for East European Management Studies, 2008)
Based on empirical research, the paper investigates two segments of the Hungarian economic elite: multipositionals - who hold three or more positions - and the leaders of transnational companies. It investigates the social characteristics and income chances of the two groups; income chances are measured in relative terms. Multipositionality was more frequent among leaders of private than state-owned companies, and less typical among managers of foreign than Hungarian companies. Multipositionals had two and a half, transnationals more than three times better income chances than the rest of the economic elite. Regression models revealed that besides multipositionality and foreign ownership, middle class social origin and a continuous career also had a positive effect on income chances. – – Die empirische Studie stellt zwei Segmente der wirtschaftlichen Elite Ungarns vor: die multipositionale Elite, Unternehmensführer mit drei oder mehr Führungspositionen, und Manager transnationaler Unternehmen. Untersucht werden soziale Merkmale und Einkommenschancen der beiden Gruppen. Über Multipositionalität verfügen häufiger Leiter privatwirtschaftlicher als Leiter staatseigener Unternehmen, häufiger Manager ungarischer als Manager ausländischer Unternehmen. Bei den Einkommenschancen hingegen haben die Manager transnationler Unternehmen es besser: Sie verfügen dreimal größere, multipositionale Manager über eine zweieinhalb Mal größere Einkommenschance als der Rest der wirtschaftlichen Elite. Regressionsmodelle zeigen, dass - neben der Multipostionalität und ausländischem Anteilsbesitz - eine mittelständische Herkunft und ein kontinuierlicher Karriereverlauf einen positiven Effekt auf die Einkommenschancen haben.
Keywords: 650; economic elite; business leaders; managers; transnational companies; multipositionality; post-socialist transformation; Hungary; income differences